การวิเคราะห์พฤติกรรมของการใช้จักรยานของสมาชิกสมาคม นักปั่นจักรยานเชียงใหม่ - พิชชาภา สุขเจริญ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research explored the cycling behavior of the cycling association of Chiang Mai, and moreover the relationship between the frequency of using cycling with the government supporting and the physical environment. A questionnaire was used as a tool to collect the data from 300 persons who are the Cycling Association of Chiang Mai. We used percentage, average and standard deviation to describe the data while chi-square was used to determine the correlation between behavior of using cycling with the government supporting and the physical environment. The results showed that the most of the response why they using cycling was they would like to go exercising by cycling. We found that the bike riders have ridden their bike over three years. The exercise duration was between four to five days a week and a half hour to one hour per day and they will ride a distance of 10 kilometers to 20 kilometers per day. The result showed that the attitude level for cycling is high and the attitude level for government supporting and physical environment is low. Finally, the attitude level for social environment is neutral. In conclusion, if there were the differences in frequency of using cycling, it would affect to the attitude level of government supporting. For physical environment, we found that quality of street, bicycle parking and traffic light for cycling were significant variables to describe that differences in frequency of using cycling can make different attitude level. For bike lane and public bath, these variables were not significant to explain the frequency of using cycling